Иммуноцитохимические показатели экспрессии мет-энкефалина в паравентрикулярных ядрах гипоталамуса при экспериментальном диабете у крыс - Абрамов, А.В.; Карнаух, М.Н. (Таврический медико-биологический вестник, 2012)
У щурів в динаміці експеріментального діабету імунофлюоресцентним методом в суб’ядрах паравентрикулярного ядра вивчено розподіл нейронів, що синтезують мет-енкефалін. Визнечені їх морфометричні характеристики й кількісні показники накопичення мет-енкефаліну. Встановлено, що при діабеті посилюється експресія, синтез і секреція мет-енкефаліну тільки в нейросекреторних суб’ядрах паравентрикулярного ядра. At rats with an experimental diabetes the distribution of met-enkephalin synthesizing neurons in the paraventricular nucleus subnuclei was studied by immunofluorescence method. It was determine morphometric characteristics, and quantitative accumulation of met-enkephalin in neurons. We observed elevating the expression, increases synthesis and secretion of met-enkephalin only in the paraventricular neurosecretory subnuclei.